2012
DOI: 10.1016/j.optmat.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

A luminescence spectroscopy study of scintillation crystals SrI2 doped with Eu2+

Abstract: We report experimental study of luminescent properties of modern scintillation material SrI 2 :Eu 2+ carried out over the temperature range from 9 to 450 K by the means of the ultraviolet and vacuum ultraviolet spectroscopy with a time resolution. Photoluminescence of the Eu 2+ ions at 2.85 eV was studied under both the intracenter and interband excitations, including an X-ray excitation. The bandgap of the SrI 2 crystal has been estimated on the basis of the obtained results. In the temperature range below 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 17 publications
4
33
0
Order By: Relevance
“…The PL emission spectrum comprises of two broad bands at 2.2 and 2.9 eV (FWHM ¼0.55 and 0.22 eV), respectively. The 2.2 eV band can be caused by crystal hydrates, that arose in the interaction of the SrI 2 surface with the water molecules as it was shown previously for SrI 2 :Eu [16]. Spectroscopic parameters of the low-intensity 2.9 eV band are the same as for the 5d-4f luminescence of Eu 2+ in SrI 2 crystals.…”
Section: Undoped Sri 2 Crystalssupporting
confidence: 62%
See 4 more Smart Citations
“…The PL emission spectrum comprises of two broad bands at 2.2 and 2.9 eV (FWHM ¼0.55 and 0.22 eV), respectively. The 2.2 eV band can be caused by crystal hydrates, that arose in the interaction of the SrI 2 surface with the water molecules as it was shown previously for SrI 2 :Eu [16]. Spectroscopic parameters of the low-intensity 2.9 eV band are the same as for the 5d-4f luminescence of Eu 2+ in SrI 2 crystals.…”
Section: Undoped Sri 2 Crystalssupporting
confidence: 62%
“…The concentration of the Nd 3+ impurity ions was chosen to make its luminescence comparable in intensity with the other PL emission bands found previously in SrI 2 crystals [16]. Data on the real structure of the grown crystals of strontium iodide were presented in a previous paper [16]. X-ray diffraction study showed that crystal structure parameters of SrI 2 :Nd crystals have no significant deviations from that of pure SrI 2 presented in Ref.…”
Section: +mentioning
confidence: 90%
See 3 more Smart Citations